The effect of high performance inulin on appetite, energy intake and anthropometric indices in patient with type 2 diabetes - Ghavami, Abed; Roshanravan, Neda; Nattagh-Eshtivani, Elyas; Sharifi, Shima; Arzhang, Peshawa; Alizadeh Sani, Mahmood; Dinarvand, Mohsen Hemmati; Shokri, Ali; Ostadrahimi, Alireza (Progress in Nutrition, 2020)
Aim: This trial was conducted to evaluate the effects of high performance inulin on anthropometric indices and appetite status in patient with type 2 diabetes. Methods: Forty six patients with type 2 diabetes were randomly assigned to two groups. Subjects received 10g/d high performance inulin (n=23) or 10 g/d placebo (n=23) for 8 week. Anthropometric indices were measured at baseline and after 8 weeks. Dietary intakes and appetite status were evaluated by food records and Visual Analogues Scale recpectivly. Results: After 8 weeks, in the high performance inulin group there were a significant decrease in waist circumference, hip circumference, energy intake and Total Satiety score compared to placebo group. Intera- group analysis showed that a significant decrease in energy intake. Conclusion: high performance inulin may improve body weight, anthropometric indices and appetite statues in type 2 diabetic patients.